Digital leadership in the economies of the G20 countries: A secondary research - Afriyadi Cahyadi; Róbert Magda (Economies, 2021)
The present research aims to identify the main peculiar economics of professional team sports, reflect on whether they apply to esports, and derive some implications. To achieve this aim, two sequential snowballing literature reviews were conducted. First, the literature on the peculiar economics of professional team sports was reviewed and assessed by the authors, based on their degree of distinctiveness and how core they are for the sector. Second, based on the main peculiar economics identified, a similar process considering economic aspects in the esports literature was conducted. The first review enabled the identification of 50 peculiar economics of professional team sports, of which 12 were assessed as the most distinctive and core to the sector. These 12 main peculiar economics were then considered in relation to the esports literature. This second review enabled the identification of some economic similarities and differences between sports and esports, before deriving some implications.
Keywords: 330; digital leadership; digital readiness; innovation; competitiveness 4.0; G20; secondary research